2012
DOI: 10.1038/nature11273
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin organization is a major influence on regional mutation rates in human cancer cells

Abstract: Cancer genome sequencing provides the first direct information on how mutation rates vary across the human genome in somatic cells. Testing diverse genetic and epigenetic features, here we show that mutation rates in cancer genomes are strikingly related to chromatin organization. Indeed, at the megabase scale, a single feature—levels of the heterochromatin-associated histone modification H3K9me3—can account for more than 40% of mutation-rate variation, and a combination of features can account for more than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

73
545
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(628 citation statements)
references
References 29 publications
73
545
0
Order By: Relevance
“…The mutation spectrum thus resembles that of mutations that occurred in germ cells and persisted in the offspring population, often with no pathogenic effects (dbSNP) but distinctly different from that of diseaseassociated mutations (ClinVar). These results are in agreement with recent findings that chromatin organization influences the genomic susceptibility to acquire somatic mutations (Michaelson et al 2012;Schuster-Bockler and Lehner 2012).…”
Section: Somatic Mutations Routinely Occur In the Blood Genomesupporting
confidence: 83%
“…The mutation spectrum thus resembles that of mutations that occurred in germ cells and persisted in the offspring population, often with no pathogenic effects (dbSNP) but distinctly different from that of diseaseassociated mutations (ClinVar). These results are in agreement with recent findings that chromatin organization influences the genomic susceptibility to acquire somatic mutations (Michaelson et al 2012;Schuster-Bockler and Lehner 2012).…”
Section: Somatic Mutations Routinely Occur In the Blood Genomesupporting
confidence: 83%
“…In addition, this study also showed that BLIMP1/ PRMT5 and histone H2A and H4 arginine 3 dimethylation are present in CIS and most seminomas, and less in EC and other nonseminomas. Recently, Schuster-Böckler and Lehner showed that chromatin organization has a major influence on regional mutation rates (Schuster-Bockler and Lehner, 2012). Mutation rates were positively correlated with heterochromatin related marks, of which histone modification H3K9Me3 was most important, and accounted for more than 40% of the somatic mutation variants (Schuster-Bockler and Lehner, 2012).…”
Section: Germ Cell Development and Gccmentioning
confidence: 99%
“…Recently, Schuster-Böckler and Lehner showed that chromatin organization has a major influence on regional mutation rates (Schuster-Bockler and Lehner, 2012). Mutation rates were positively correlated with heterochromatin related marks, of which histone modification H3K9Me3 was most important, and accounted for more than 40% of the somatic mutation variants (Schuster-Bockler and Lehner, 2012). The open chromatin in regions involved in embryonic development showed a negative association, which is in line with the fact that mutations are rarely found in GCC and the idea that the germ line is protected for mutations (immortal strand).…”
Section: Germ Cell Development and Gccmentioning
confidence: 99%
“…14,16 Transcription of satellite DNA is naturally repressed by the compact structure of heterochromatin; thus, its overexpression has been associated with genomic instability. 17,18 The implications of heterochromatin structure in human cancer have been recently highlighted by the dramatic correlation between the mutation rates of the cancer genome and heterochromatin, 19 and by the overexpression of heterochromatic satellite DNA sequence in diverse mouse and human cancers. 20 In the present study, we identify a link between PTEN and heterochromatin.…”
Section: Introductionmentioning
confidence: 99%